PENJERNIHAN AIR DI DESA TANJUNG PERING, KECAMATAN INDERALAYA UTARA, KABUPATEN OGAN ILIR - Marieska Verawati; Eka Kandi Lidiasari; Parwiyanti Kandi Parwiyanti; Friska Syaiful (Politeknik Negeri Sriwijaya, 2019)
Tanjung Pering Village, one of fostered villages under Sriwijaya University development programs, is a village partner for this community service (PPM) activities as part of The Higher Degree Education Devotion for Community or Tri Dharma Perguruan Tinggi. The village is located 40 km from Palembang City and 8 km from the Sriwijaya University Indralaya campus. The village is part of the North Inderalaya District that is located in Ogan Ilir Regency, South Sumatra Province. The area of Tanjung Pering Village is ± 29.75 Km2 or around 6% of the area of North Inderalaya District. The population of Tanjung Pering Village in 2017 was 1,720 people, with a composition of 859 men and 861 women. The population of this village mostly still uses water from wells that poor in quality that is characterized by its yellowish color and rusted smells. The purpose of this activity is for introducing and training the community in the manufacturing a simple water purification equipment. This program was targeted to delivere a solution for the community in providing the need for clean water for their daily needs.